Choosing a Vibratory Test to Pair With Semmes Weinstein Monofilament Testing for Evaluating Lower Extremity Sensation in Patients With Diabetes: A Comparison of Three Vibratory Methodologies. (January 2020) - Raymond, Bryan; Steriovski, James; Gillyard, KaNesha; Yang, Chalen; Wu, Stephanie C.; Crews, Ryan T.
Background: Numerous guidelines recommend pairing Semmes-Weinstein monofilament (SWM) testing with a secondary clinical test when screening for diabetic peripheral neuropathy, yet time is very limited in clinical practice. This study compared the time to complete and the diagnostic agreement of three vibratory sensation tests. Methods: Sixty-five individuals (42% male; aged: 61 ± 12 years) were recruited. A single investigator administered the following tests bilaterally: 10-site SWM, traditional tuning fork (TTF), electronic tuning fork (ETF), and vibration perception threshold (VPT) via biothesiometer. Times to physically administer the tests were compared with a one-way repeated measures ANOVA. Cochran's Q test was used to compare the varied tests' diagnostic agreement. Results: The ANOVA indicated there were significant ( P < .001, partial eta squared = .442) differences in time to complete the varied tests. Sidak post hoc comparisons indicated the VPT (21.2 ± 14.3) testing took an intermediate time to complete, while the ETF (9.7 ± 6.5) and TTF (10.1 ± 7.5) tests took the least amount of time, and the SWM (28.6 ± 8.4) test took the longest time. There were also numerous significant differences ( P ≤ .001) between the different tests in regards to neuropathy diagnoses. Conclusions: Tuning fork methods required 11 seconds less to administer than VPT testing. Although that may seem trivial, it is worth noting peripheral neuropathy screening often fails to occur in the precious few minutes clinicians are allotted per patient. Considering ETF's intrinsic control of stimulus amplitude and its ease of use with an embedded timer, the ETF is recommended over the TTF. Clinicians should also be mindful that different tests yield different diagnostic conclusions.